Incidence and Predictors of Subsequent Surgery After Anterior Cruciate Ligament Reconstruction: A 6-Year Follow-up Study. Issue 10 (August 2020) - ; Sullivan, Jaron P.; Huston, Laura J.; Zajichek, Alexander; Reinke, Emily K.; Andrish, Jack T.; Brophy, Robert H.; Dunn, Warren R.; Flanigan, David C.; Kaeding, Christopher C.; Marx, Robert G.; Matava, Matthew J.; et al.
Background: The cause of subsequent surgery after anterior cruciate ligament (ACL) reconstruction varies, but if risk factors for specific subsequent surgical procedures can be identified, we can better understand which patients are at greatest risk. Purpose: To report the incidence and types of subsequent surgery that occurred in a cohort of patients 6 years after their index ACL reconstruction and to identify which variables were associated with the incidence of patients undergoing subsequent surgery after their index ACL reconstruction. Study Design: Cohort study; Level of evidence, 2. Methods: Patients completed a questionnaire before their index ACL surgery and were followed up at 2 and 6 years. Patients were contacted to determine whether any underwent additional surgery since baseline. Operative reports were obtained, and all surgical procedures were categorized and recorded. Logistic regression models were constructed to predict which patient demographic and surgical variables were associated with the incidence of undergoing subsequent surgery after their index ACL reconstruction. Results: The cohort consisted of 3276 patients (56.3% male) with a median age of 23 years. A 6-year follow-up was obtained on 91.5% (2999/3276) with regard to information on the incidence and frequency of subsequent surgery. Overall, 20.4% (612/2999) of the cohort was documented to have undergone at least 1 subsequent surgery on the ipsilateral knee 6 years after their index ACL reconstruction. The most common subsequent surgical procedures were related to the meniscus (11.9%), revision ACL reconstruction (7.5%), loss of motion (7.8%), and articular cartilage (6.7%). Significant risk factors for incurring subsequent meniscus-related surgery were having a medial meniscal repair at the time of index surgery, reconstruction with a hamstring autograft or allograft, higher baseline Marx activity level, younger age, and cessation of smoking. Significant predictors of undergoing subsequent surgery involving articular cartilage were higher body mass index, higher Marx activity level, reconstruction with a hamstring autograft or allograft, meniscal repair at the time of index surgery, or a grade 3/4 articular cartilage abnormality classified at the time of index ACL reconstruction. Risk factors for incurring subsequent surgery for loss of motion were younger age, female sex, low baseline Knee injury and Osteoarthritis Outcome Score symptom subscore, and reconstruction with a soft tissue allograft. Conclusion: These findings can be used to identify patients who are at the greatest risk of incurring subsequent surgery after ACL reconstruction.